Apoptotic and Necroptotic Mediators are Differentially Expressed in Mucinous and Non-Mucinous Colorectal Cancer - O’Connell, Emer; Reynolds, Ian S.; Lindner, Andreas U.; Salvucci, Manuela; O’Grady, Tony; Bacon, Orna; Cho, Sanghee; McDonough, Elizabeth; Longley, Daniel; Ginty, Fiona; McNamara, Deborah A.; Burke, John P.; et al. (Frontiers in Oncology, 2022)
Background Mucinous colorectal cancer (CRC) represents 10% of all CRC and is associated with chemotherapy resistance. Apoptosis and necroptosis pathways remain poorly understood in the mucinous subtype. Methods Protein levels were analysed in SW1463 (mucinous rectal), SW837 (non-mucinous rectal), LS174T (mucinous colon) and HCT116 (non-mucinous colon) cell lines by western blot. Cell death was analysed by flow cytometry. RNA gene expression data were extracted from TCGA. Protein levels in mucinous and non-mucinous tumors were measured by multiplexed immunofluorescence. Results Western blot of cell lines identified alterations in apoptosis proteins in mucinous CRC, most prominently downregulation of Bcl-xL protein levels (p=0.029) which was also observed at the mRNA level in patients by analysis of TCGA gene expression data (p<0.001). Bcl-xL reduction was accompanied by high basal levels of apoptosis in mucinous cell lines and in resected mucinous rectal tumors. Treatment with 5-FU did not significantly elevate cell death in mucinous cells, while non-mucinous cells showed robust cell death responses. However, 5-FU-induced phosphorylation of MLKL in mucinous cancer cells, suggestive of a switch to necroptotic cell death signaling. Conclusion Distinctions between mucinous and non-mucinous CRC extend to cell death signaling with differential expression of mediators of the mitochondrial apoptosis and necroptosis pathways.